2012
DOI: 10.2298/vsp1211967s
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic stability in total intravenous propofol anesthesia with midazolam coinduction versus general balanced anaesthesia in laparoscopic cholecystectomy

Abstract: Total intravenous anesthesia with propofol provides better hemodynamic stability for ASA III patients with concomitant cardiovascular diseases then GBA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
(12 reference statements)
0
4
0
Order By: Relevance
“… 7 TIVA has been shown to provide better hemodynamic stability when compared to GA in a study of patients undergoing laparoscopic cholecystectomy. 12 Studies have also demonstrated that inhaled anesthetics can impair cerebral autoregulation, while intravenous agents, such as propofol, preserve it. 11 Therefore, TIVA may be a safer option for patients undergoing shoulder arthroscopy in the beach chair position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 TIVA has been shown to provide better hemodynamic stability when compared to GA in a study of patients undergoing laparoscopic cholecystectomy. 12 Studies have also demonstrated that inhaled anesthetics can impair cerebral autoregulation, while intravenous agents, such as propofol, preserve it. 11 Therefore, TIVA may be a safer option for patients undergoing shoulder arthroscopy in the beach chair position.…”
Section: Discussionmentioning
confidence: 99%
“… 6 While studies have demonstrated that inhaled anesthetics can impair cerebral autoregulation, intravenous agents, such as propofol, have been shown to preserve it. 12 However, one concern with TIVA is patient alertness, with most cases of self-reported awareness occurring in patients who received a neuromuscular blocking drug. 8 Therefore, processed EEG monitoring is recommended when a neuromuscular blocking drug is used with TIVA.…”
mentioning
confidence: 99%
“…Hemodynamic and respiratory stability in anaesthesia is crucial in response to all the perioperative influences, including hypothermia 19 . Even mild hypothermia may lead to cardiovascular impairments such as postoperative increase in heart rate and blood pressure, increase in vascular resistance, ventricular dysrrhytmia and irritability, and myocardial depression 20 .…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] In contrast, the possibility of liver damage from anesthetic metabolites is expected to be lower for total intravenous anesthesia (TIVA) with propofol; moreover, hemodynamic stability is noted for TIVA with propofol. 8 In addition, propofol is an excellent anesthetic agent for patients with liver disease because of its short half-life even in patients with decompensated cirrhosis. 9 Therefore, TIVA with propofol is likely to be safer in patients with preoperatively elevated liver transaminase levels, which might suggest liver damage.…”
Section: Introductionmentioning
confidence: 99%